Effect of phenolic extracts on trans fatty acid formation during frying - TH Gamel (Grasas y Aceites, 1999)
Olive oil (blend of refined and virgin) and sunflower oil containing added methanol phenolic extracts of dry rosemary and olive vegetable water or the synthetic antioxidant BHA in combination with the extracts, were used in a frying process. Eight frying operations were performed at 180 °C with 24 hr intervals between fryings. During the frying period the trans fatty acids (TFA) by capillary column gas chromatography (CC-GC) were determined. Trans fatty acids of oleic and linoleic were increased with frying time in both the control oil samples. The rosemary additives (extracts) alone and in combination with BHA decreased the level of trans fatty acids (mainly elaidic acid), while the addition of olive vegetable water did not have any effect.